Severe course of influenza B complicated by rhabdomyolysis and acute respiratory failure resulting in death - Sagan, Jiří; Širůček, Petr; Folwarczny, Pavel; Sporková, Marie; Hurník, Pavel (Klinicka mikrobiologie a infekcni lekarstvi, 2018)
Influenza is an acute viral disease that causes influenza A, B, C. Clinically, flu is typically characterized by fever and respiratory symptoms, sometimes with the need for mechanical ventilation, less frequently by gastrointestinal symptoms and muscle problems; severe are cases with central nervous system involvement. The most common complication of influenza is secondary bacterial infection, typically pneumonia, which is most frequently caused by pneumococci and staphylococci. Every year, thousands of patients die of influenza or its complications. In the Czech Republic, namely the Moravian-Silesian Region, influenza B virus dominated the 2017/2018 flu season. Presented is a case of a 51-year-old male with influenza B as an etiologic agent of rapidly progressing muscle weakness and laboratory tests showing rhabdomyolysis and significantly elevated muscle enzyme and aminotransferase, resulting in acute respiratory failure and death.
Keywords: Influenza, Human; respirační insuficience; Middle Aged; umělé dýchání; mužské pohlaví; Respiratory Insufficiency; Humans; Rhabdomyolysis; rhabdomyolýza; Fatal Outcome; Czech Republic; chřipka lidská; lidé středního věku; fatální výsledek; lidé; Male; Respiration, Artificial; Česká republika